Variants of CARD14 gene and psoriasis vulgaris in southern Chinese cohort - Kunju Zhu; Ge Shi; Huan Liu; Chengyao Zhu; Yiming Fan (Sociedade Brasileira de Dermatologia, 2016)
Abstract BACKGROUND: Recent mutation analysis identified several missense mutations in CARD14 in psoriasis. OBJECTIVES: We performed the genomic sequence analysis on CARD14 in southern Chinese Han Cantonese with Psoriasis Vulgaris (PsV) to reveal more causative missense mutations. METHODS: A total of 131 patients with PsV and 207 matched controls were included. We conducted sequence analysis of all the exon and exon-intron boundaries of CARD14 in the group of PsV patients and subsequent case control analysis of potential sequence variants of significance. RESULTS: We found five rare mutations and four of them are annotated or reported. Only the variant (c.1291C>G) has not been reported and annotated, but the variant was also found in controls. No significant difference was detected among all rare variant allele frequencies of patients and controls. CONCLUSION: None of the new definite variants were pathogenic. The other pathogenic mutations for PsV are still elusive in our cohort.